Statistical significance of indicators of efficiency and incentives: Examples from West African agriculture - McIntire, John M.; Delgado, Christopher L. (Wiley, 1985)
Illustrates the practical advantages of considering the usual indicators as random variables, using farm data from semiarid West Africa. Defines four indicators in comon use and discusses their random character. Presents an estimation of population parameters of the indicators from sample survey data in Burkina Faso and Niger. Also illustrates the consequences of ignoring statistical variability.